From Urbex places to official walls in the cities in France: the liminal circulation of street art, from illegal to legal - Vincent, Lambert; Christian, Gerini (Street Art & Urban Creativity, 2023)
Many street artists started their practice as vandals on walls, trains, etc. But we often forget what they did in abandoned places called Urbex. It is in such places that we have been working for many years in proximity, exchanging and sharing with these artists, some of whom have gained recognition in the art world or in urban politics. This fieldwork is both a work about history of contemporary art and an anthropological study. It has enabled us to highlight the need for these artists to remain between the two worlds: that of known and recognized art and that of their origins, i.e. illegal, hidden and free. We give an overview here with examples of Urbex locations and artists from the south of France. But we also show the discomfort they feel in the "cultural third places" where their freedom is often limited by those who finance these places.